Study of control signal for Quadrotor UAV - Hazry, Desa; Mohd Sofian, Muhamad Rosbi; Muhamad Firdaus, Muhamad Dali (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.